Delftibactin-A, a Non-ribosomal Peptide With Broad Antimicrobial Activity - Tejman-Yarden, Noa; Robinson, Ari; Davidov, Yaakov; Shulman, Alexander; Varvak, Alexander; Reyes, Fernando; Rahav, Galia; Nissan, Israel (Frontiers in Microbiology, 2019)
The rapid emergence of drug resistant bacteria is occurring worldwide, outpacing the de-velopment of new antibiotics. It is known that some of the main sources of antibiotics are the bacteria themselves, many of which are secondary metabolites of Gram positive bacte-ria. Siderophores, which are secondary metabolites, function as natural ion chelators (e.g. iron). They are produced and secreted by many bacteria and have been experimented on as "carriers" of several types of antibiotics that pass the cell membrane of challenging Gram negative bacteria. Delftibactin A is a non-ribosomal peptide (NRP), which is known to detoxify gold in Delftia spp. and form gold nuggets, and is considered to be a siderophore. In this study we demonstrate that the supernatant from novel environmental isolates of Delftia spp. have antimicrobial activity. We characterized the active fraction and identified delftibactin A as a compound with antimicrobial activity. Delftibactin A exhibits potent antimicrobial activity against Gram positive multi drug resistant (MDR) bacteria like Methicillin-resistant Staphylococcus aureus (MRSA), and Vancomycin re-sistant Enterococcus (VRE), and also against the Gram negative pathogen Acinetobacter baumannii and Klebsiella pneumoniae. We discovered that the production of delftibactin A is greatly influenced by temperature. Furthermore, we have demonstrated the possibility of utilizing delftibactin A as a siderophore carrier of toxic metals such as gallium into Gram negative bacteria. These findings expose new opportunities of yet unexploited natural products such as delftibactin A, which have been known for other bacterial uses, as potent factors in the battle against MDR bacteria.